An FFT overlap method for high bandwidth far-infrared laser Interferometer in HL-2A. (13th September 2021) - Zhang, W.; Wu, T.Y.; Li, Y.G.; Zhang, Y.P.
Abstract: A novel Real-Time High Bandwidth Phasemeter (RHBP) system has been developed for far-infrared laser interferometer in HL-2A tokamak. To meet the requirement of high-precision electron density fluctuation diagnostics, the system is based on the FFT overlap method, which can suppress the measurement error in high-bandwidth mode. The system consists of four Real-time Signal Conditioning (RSC) Modules and four RHBP Modules for high spatial resolution. Benefiting from the field-programmable gate array (FPGA) platform, the proposed method can be implemented with low noise and low cost. Experimental results suggest that the density resolution is 1.79× 10 15 /m -3 in high-bandwidth mode, which indicates that the proposed RHBP system achieves high performance for high-frequency fluctuation measurement.